2015
DOI: 10.1016/j.eats.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Primary Frozen Shoulder Syndrome: Arthroscopic Capsular Release

Abstract: Idiopathic adhesive capsulitis, or primary frozen shoulder syndrome, is a fairly common orthopaedic problem characterized by shoulder pain and loss of motion. In most cases, conservative treatment (6-month physical therapy program and intra-articular steroid injections) improves symptoms and restores shoulder motion. In refractory cases, arthroscopic capsular release is indicated. This surgical procedure carries several advantages over other treatment modalities. First, it provides precise and controlled relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…In 1970, Neer [16] first proposed the term "rotator interval" (RI) to describe the histological structure between supraspinatus tendon and subscapularis tendon, consisting of the coracohumeral ligament (CHL), the superior glenohumeral ligament (SGHL) and a part of the anterior articular capsule, and verified that the RI played a role in maintaining shoulder joint stability in subsequent studies with Foster [17]. Since Neer's study, Neer et al [18] reported in 1992 that the CHL played an important limiting role on the external rotation of the shoulder joint; CHL release or amputation for patients with frozen shoulder joint obstruction during external rotation began clinically, having significant influences on the long-term anterior shoulder stability [2,11,14]. In this study, the length, width and thickness of the CHL at a specific position of the shoulder joint are measured anatomically, and changes in tension are described by observing the contraction state, with a view to illuminate the specific action mechanisms of CHL on maintaining shoulder joint stability.…”
Section: Sun Et Al Coracohumeral Ligamentmentioning
confidence: 86%
“…In 1970, Neer [16] first proposed the term "rotator interval" (RI) to describe the histological structure between supraspinatus tendon and subscapularis tendon, consisting of the coracohumeral ligament (CHL), the superior glenohumeral ligament (SGHL) and a part of the anterior articular capsule, and verified that the RI played a role in maintaining shoulder joint stability in subsequent studies with Foster [17]. Since Neer's study, Neer et al [18] reported in 1992 that the CHL played an important limiting role on the external rotation of the shoulder joint; CHL release or amputation for patients with frozen shoulder joint obstruction during external rotation began clinically, having significant influences on the long-term anterior shoulder stability [2,11,14]. In this study, the length, width and thickness of the CHL at a specific position of the shoulder joint are measured anatomically, and changes in tension are described by observing the contraction state, with a view to illuminate the specific action mechanisms of CHL on maintaining shoulder joint stability.…”
Section: Sun Et Al Coracohumeral Ligamentmentioning
confidence: 86%
“…This method is standardized and adopted for all patients undergoing arthroscopic capsular release in this institution and is a widely used approach. 20,21 First, an inspection of the glenohumeral joint is done via the posterior viewing portal ( Fig. 2A).…”
Section: Methodsmentioning
confidence: 99%
“…ACR can be performed in the beach-chair (BC) position 1 as well as in the lateral decubitus (LD) position. 11,27 Typically, surgeon preference for patient positioning is based on training, experience and the intended procedure.…”
mentioning
confidence: 99%